Regulation of Public Finances in Serbia in Light of Financial Constitutionality - Milošević, Goran (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
A country has always been an important factor in the economic processes of a county. With its activity, mechanisms for provision of services, consumption and investment system, its role in the allocation and distribution process of income and wealth, a country directly or indirectly establishes certain relations in the social reproduction process. Because of that it can be said that the country activity reflects on the public, but also on the private sector of a social community. No government, no county, can afford the ease of economic and any other activity taking place past it. A country must take on a lot of tasks, to establish the necessary harmony in all spheres of social activities in a social community. For realization of numerous tasks that are entrusted to one country, it needs certain funds that it collects either with the monopoly of its sovereign authority or in some other way. With the change and development of the county the tax system which is necessary to fulfil its role also changed and developed. In the field of taxation, the Republic of Serbia has no limitations on the scope of its tax jurisdiction. The constitution regulates the subjective financial law of the country, i.e., the right to introduce and collect taxes and prescribe the duty of natural and legal entities to act in accordance with tax regulations. Modern constitutions have established the principle of legality of taxes, which can be expressed by the maxim ‘nullum tributum sine lege’ (‘there is no tax without law’). Thus, Article 91, paragraph 1 of the Constitution of Serbia prescribes that the funds from which the jurisdiction of the Republic of Serbia, autonomous provinces and local self-government units are financed, are provided from taxes and other revenues determined by law. Paragraph 2 of the same article proclaims the rule that the obligation to pay taxes and other duties is general and is based on the economic power of the taxpayer. Therefore, the basic postulates on which the financial right is built are contained in the constitution. It follows that financial law cannot exist without constitutional norms. On the other hand, through tax law, the constitution gained its concretization and realization. The science of financial law is exhibited in numerous monographs, textbooks, studies, discussions, articles, and other publications. Several authors have made a great contribution to the development of this scientific discipline in Serbia, among which the most important are Milan Todorović, Jovan Lovčević, Aleksandar Perić, Miodrag Jovanović, Miroslav Petrović, Dejan Popović, Božidar Raičević, and others.KEYWORDS: Constitution, law, tax system, tax jurisdiction, fiscal rules, public revenues, taxes, contributions, fees, excise duties, customs, tax procedure, tax determination, tax collection, tax control.